Design of 4-(4-dialkylaminostyryl) -pyridinium dyes for fluorescent detection of amyloid fibrils - Inshyn, D.I.; Chernii, S.V.; Kovalska, V.B.; Yarmoluk, S.M. (Вiopolymers and Cell, 2016)
The pathological proteins aggregation into the fibrillar structures is common to a large group of amyloid-related disorders, such as neurodegenerative diseases. Accordingly, there is a need for development of analytical tools, particularly fluorescent probes for detection of amyloid fibrils. Aim. To design amyloid-sensitive styrylpyridinium fluorescent dyes. Methods. QSAR model for the prediction of the dye efficiency followed by the synthesis and spectral-luminescent studies. Results. Nine structures with the highest predicted efficiency were selected from the virtual database of 1500 styrylcyanines; these compounds were synthesized and their spectral-luminescent properties in the presence of amyloidogenic protein insulin were studied. The dyes are weakly fluorescent when free and have a low sensitivity to native insulin. In the presence of insulin fibrils, they increase the fluorescence intensity up to dozens of times depending on the nature of the terminal substituent. The dye with a 4-methylpiperidinyl substituent demonstrated the highest fluores-cence response (up to 23 times) and a wide range of fibril detection (1–40 μg/ml). Conclusion. (4-(4-dialkylaminostyryl) -pyridinium dyes with cyclic aliphatic terminal substituent have the properties of fluorescent probes for sensing the amyloid fibrils. The prediction accuracy of the regression model is suitable for the majority of the styrylcyanines but poor in the case of the dyes with piperazinyl substituent or those containing additional aromatic substituents. детектувати амілоїдні фібрили. Мета. дизайн амілоїд-чутливих стирилпіридинових флуоресцентних барвників. Методи. Метод QSAR для передбачення чутливості барвників до амілоїдних фібрил, хімічних синтез, спектральні дослідження . Результати. Із віртуальної бази на 1500 стирилціанінів були обрані дев’ять структур із найвищою передбаченою ефективністю. Обрані сполуки були синтезовані, їх спектрально-люмінесцентні властивості були вивчені у присутності амілоїдогенного білка інсуліну. Ці барвники мають низьку власну флуоресценцію та низьку чутливість до мономерного інсуліну. У присутності фібрилярного інсуліну вони можуть збільшувати інтенсивність флуоресценції до десятків разів залежно від природи кінцевого замісника в молекулі барвника. Барвник із 4-метилпіридиновим замісником має найвищу флуоресцентну відповідь (до 23 разів) і широкий діапазон детекції амілоїд них фібрил (1–40 мкг / мл). Висновки. (4-(4- диалкіламіностирил) -піридинові барвники з циклічними аліфатичними кінцевими замісниками демонструють перспективні властивості як флуоресцентні зонди для детекції амілоїдних фібрил. Регресійна модель показала хорошу точність передбачення для більшості барвників, виключенням є стирилціаніни, що містять піперазиніловий та інші ароматичні замісники. Патологическая агрегация белков в бета-складчатые фибриллярные структуры связана с большой группой тяжелых заболеваний, в частности, нейродегенеративных расстройств. В связи с этим актуальной является разработка аналитических инструментов, к примеру, флуоресцентных зондов, позволяющих детектировать амилоидные фибриллы. Цель. дизайн амилоид-чувствительных стирилпиридиновых флуоресцентных красителей. Методы. Метод QSAR для предсказания чувствительности красителя к фибриллам, синтез, спектральные исследования. Результаты. Из виртуальной базы на 1500 стирилцианинов были выбраны девять структур с высокой прогнозированной эффективностью. Эти соединения были синтезированы, их спектрально-люминесцентные свойства были изучены в присутствии амилоидогенного белка инсулина. Красители показали низкую собственную флуоресценцию и низкую чувствительность к мономерному инсулину. В присутствии фибриллярного инсулина они могут увеличивать интенсивность флуоресценции до десятков раз в зависимости от природы концевого заместителя в молекуле красителя. Краситель с 4-метилпиридиновым заместителем дает самый высокий флуоресцентный ответ (до 23 раз) и широкий диапазон детекции амилоидных фибрил (1–40 мкг / мл). Выводы. (4-(4-диалкиламиностирил)-пиридиновые красители с циклическими алифатическими конечными заместителями демонстрируют перспективные свойства как флуоресцентные зонды для детекции амилоидных фибрилл. Регрессионная модель показала хорошую точность предсказания для большинства стирилцианинов, за исключением красителей содержащих пиперазиниловий и другие ароматические заместители.